The role of the pAbp gene encoding the cytoplasmic poly(A)-binding protein in spermatogenesis of Drosophila melanogaster - E. U. Bolobolova; E. M. Baricheva; N. V. Dorogova (Вавиловский журнал генетики и селекции)
The Drosophila melanogaster pAbp gene encodes the cytoplasmic poly(A)-binding protein (PABP). Cytoplasmic PABPs participate in the metabolic pathways of the mRNA: translation initiation and termination, cytoplasmic polyadenylation/deadenylation, mRNA stability, mRNA degradation. Despite the extensive biochemical and structural characterization, relatively little is known about the biological roles of PABPs in the processes of cellular development and diﬀerentiation. In Drosophila spermatogenesis, posttranscriptional mechanisms of gene regulation play an important role, so cytoplasmic PABP can have signiﬁcant function in this process. Deletion of PABP leads to embryonic lethality. However, some ﬂies carrying combinations of mutant pAbp alleles survive but display male sterility and show defects in spermatogenesis. It has previously been shown that hypomorphic pAbp mutations cause a number of meiotic defects, abnormalities of Nebenkern formation. These data provide an insight into the eﬀect of pAbp mutation on the individual events of spermatogenesis, but they do not cover the entire process. We studied spermatogenesis in pAbpallele heterozygotes by transmission electron and ﬂuorescent light microscopy. We showed that cellular mitochondria were the primary structural target of the mutation. Abnormal mitochondria were less structured, swollen, had transparent matrix and depleted cristae. Further mutation had a polymorphous eﬀect and induced anomalies in the ultrastructure of mature spermatocytes, defects in Nebenkern formation and division, axial complex formation, shutdown of spermatogenesis during spermatid elongation. Thus our data show a signiﬁcant role of PABP in structural transformations of male germ cells during entire spermato-genesis.